Laissez-Faire Leadership Style and Its Impact on Safety Behavior Among Paramedics in the Klang Valley - Romli, Jamaludin Nasir (Management Research Journal, 2024)
This study examines the impact of the laissez-faire leadership style on safety behavior among ambulance paramedics in the Klang Valley. Through data analysis, the study results indicate a very high evaluation of this leadership style, with an average mean of 4.62, suggesting a strong tendency to allow individual freedom without significant managerial intervention. The respondents showed high satisfaction with the existing way of working and tended to be less concerned with the actions of others unless they were considered important. However, the lack of active supervision associated with the laissez-faire leadership style potentially increases safety risks, especially in situations where strict adherence to safety procedures is critical. This article discusses the implications of the study's findings on paramedic operational safety and the need for improvements in organizational supervision structures. By assessing the impact of the laissez-faire leadership style on safety behavior, this study guides enhancing safety management and operational effectiveness of paramedics in the Klang Valley.